Diurnal variation in performance of competitive swimmers - Rodahl, A.; O'Brien, M.; Firth, P. G. (The Journal of Sports Medicine and Physical Fitness, 1976)
Investigations shoed that the swimmers' performance depends on the time of the day (examples).